Imaging follow-up strategy after endovascular treatment of Intracranial aneurysms: A literature review and guideline recommendations - Cho, Yong-Hwan; Choi, Jaehyung; Huh, Chae-Wook; Kim, Chang Hyeun; Chang, Chul Hoon; KWON, Soon Chan; Kim, Young Woo; Sheen, Seung Hun; Park, Sukh Que; Ko, Jun Kyeung; Ha, Sung-kon; Jeong, Hae Woong; et al. (Journal of cerebrovascular and endovascular neurosurgery, 2024)
Objective: Endovascular coil embolization is the primary treatment modality for intracranial aneurysms. However, its long-term durability remains of concern, with a considerable proportion of cases requiring aneurysm reopening and retreatment. Therefore, establishing optimal follow-up imaging protocols is necessary to ensure a durable occlusion. This study aimed to develop guidelines for follow-up imaging strategies after endovascular treatment of intracranial aneurysms.Methods: A committee comprising members of the Korean Neuroendovascular Society and other relevant societies was formed. A literature review and analyses of the major published guidelines were conducted to gather evidence. A panel of 40 experts convened to achieve a consensus on the recommendations using the modified Delphi method.Results: The panel members reached the following consensus: 1. Schedule the initial follow-up imaging within 3-6 months of treatment. 2. Noninvasive imaging modalities, such as three-dimensional time-of-flight magnetic resonance angiography (MRA) or contrast-enhanced MRA, are alternatives to digital subtraction angiography (DSA) during the first follow-up. 3. Schedule mid-term follow-up imaging at 1, 2, 4, and 6 years after the initial treatment. 4. If noninvasive imaging reveals unstable changes in the treated aneurysms, DSA should be considered. 5. Consider late-term follow-up imaging every 3–5 years for lifelong monitoring of patients with unstable changes or at high risk of recurrence.Conclusions: The guidelines aim to provide physicians with the information to make informed decisions and provide patients with high-quality care. However, owing to a lack of specific recommendations and scientific data, these guidelines are based on expert consensus and should be considered in conjunction with individual patient characteristics and circumstances.